DETERMINAN FAKTOR INTERNAL PERUSAHAAN DALAM PENGUNGKAPAN RISIKO BISNIS DI BURSA EFEK INDONESIA - Saputra, I Wayan Aris; Purbawangsa, IB Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This research want to confirm and explore the impact of corporate internal factor that agency theory explained related to their influence on business risk disclosure in Indonesia. Factor that explained by agency theory that determine business risk disclosure  is company size, leverage, diversification, profitability, and industry type. Population on this research is all the company that listed on Indonesia Stock Exchange in 2018 that consist of 525 companies. Sample determined using purposive sampling method with 55 company as final sample. Indicator that proxy the factor will be tested first using Confirmatory Factor Analysis. This research  using Multiple Linier Regression to test the hypothesis.  The result of this research show that company size, leverage, and industry type have positif impact to business risk disclosure. Diversification and profitability don’t have significan impact to business risk disclosure. Researcher expect the result of this research contributing as a newer literature as an empirical study related to business risk disclosure and can be reference for companies for make a proper business risk disclosure.